PEMANFAATAN INTERNET OLEH MAHASISWA UNJ - Khaerudin Khaerudin (Perspektif Ilmu Pendidikan, 2007)
This research aimed at describing how the students of State University of Jakarta utilize the internet in searching information and instructional materials for their study. Using survey descriptive method, the research was conducted in the State University of Jakarta as from October through December 2006. Samples were determined by cluster random sampling technique and data were collected by using questioners and analyze by using quantitative descriptive statistics. The findings of the research indicate that almost all the student (98,1%) ever uses the internet as a learning resource and the most visited site in science (78,1%). Most of the students (83,41%) admit that they use internet to complete the tasks given by the lectures. But majority of the students (90,48%) use the internet outside of the campus as the find the facilities are not in the campus.